2006
DOI: 10.1007/s00167-006-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of accelerated, brace free, rehabilitation on bone tunnel enlargement after ACL reconstruction using hamstring tendons: a CT study

Abstract: The mechanism of bone tunnel enlargement following anterior cruciate ligament (ACL) reconstruction is not yet clearly understood. Many authors hypothesized that aggressive rehabilitation protocols may be a potential factor for bone tunnel enlargement, especially in reconstructions performed with hamstrings autograft. The purpose of this study was to evaluate the effect of a brace free rehabilitation on the tunnel enlargement after ACL reconstruction using doubled semitendinosus and gracilis tendons (DGST): our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 29 publications
0
91
0
4
Order By: Relevance
“…Vadalà et al [31] also used CT to exactly determine the diameters of both femoral and tibial tunnels at various levels of the lateral femoral condyle and proximal tibia and demonstrated that early post-operative knee motion increases the diameters of the tibial and femoral bone tunnels. Interestingly, in the proximal site of the femoral tunnel or the tibial tunnel in our study, we found no significant difference of the bone tunnel area between groups on the CT images.…”
Section: Discussionmentioning
confidence: 99%
“…Vadalà et al [31] also used CT to exactly determine the diameters of both femoral and tibial tunnels at various levels of the lateral femoral condyle and proximal tibia and demonstrated that early post-operative knee motion increases the diameters of the tibial and femoral bone tunnels. Interestingly, in the proximal site of the femoral tunnel or the tibial tunnel in our study, we found no significant difference of the bone tunnel area between groups on the CT images.…”
Section: Discussionmentioning
confidence: 99%
“…Vadalà et al 11 randomized forty-five patients after ACL reconstruction with hamstring autograft to either accelerated brace-free rehabilitation (immediate knee motion, weightbearing as tolerated on postoperative day two, immediate isometric and isotonic exercises), or standard rehabilitation (two weeks of bracing and isometric exercises, then active knee motion until six weeks, when isotonic and isokinetic exercises were initiated). The authors used computed tomography to calculate tibial and femoral tunnel diameters immediately postoperatively and at ten months of follow-up.…”
Section: Postoperative Bracingmentioning
confidence: 99%
“…Since 2005, numerous studies have evaluated the safety of accelerated and brace-free rehabilitation protocols that attempt to return athletes to sports more quickly [3][4][5][6][7][8][9][10][11] . Several studies investigated the use of bracing for additional benefits such as pain control [12][13][14] .…”
mentioning
confidence: 99%
“…According to many other authors [11,16,23,25], this study suggests how, at a short term follow up, this phenomenon is not strictly correlated with unsatisfactory clinical outcomes; however, it could often represent a further concern for the surgeon, especially in the case of ACL revision. At the present time, several biological and Fig.…”
Section: Discussionmentioning
confidence: 98%